The effects of empagliflozin in patients with type 1 diabetes: Results of a 12-week, double-blind, randomized, placebo-controlled clinical trial - Mostafa Najafipour; Farzad Najafipour; Alireza Ostadrahimi; Maryam Ghavami; Zohreh Razaghi; Helda Tutunchi; Naimeh Mesri Alamdari (Health Promotion Perspectives)
Background: Sodium-glucose cotransporter-2 (SGLT-2) acts as a key element in the reabsorption of glucose in the kidney. Currently, SGLT-2 inhibitors are FDA-approved for the treatment of type 2 diabetes. It is suggested that the mechanism of action may operate in the treatment of type 1 diabetes mellitus (T1DM), as well. This study aimed to evaluate the application of empagliflozin as an adjunctive to insulin in patients with T1D. Methods: In this double-blind placebo-controlled randomized clinical study, 60 type 1 diabetic patients were randomly assigned to have either once-daily empagliflozin 10 mg or placebo, as an addition to insulin for 12 weeks. The hemoglobin A1C, fasting blood sugar (FBS), 2-hour post-prandial blood sugar, and anthropometric indices were measured before and after 12 weeks intervention. Results: After 12 weeks, empagliflozin resulted in significant reductions of hemoglobin A1C -0.18 (95% CI: -0.37, 0.005, P=0.009), FBS –2.60 mg/dL (95% CI: -6.48, 1.28, P=0.035), 2-hour post-prandial blood sugar -22.56 mg/dL (95% CI: -35.15, 8.97, P<0.0001), and total daily insulin dose –7.6 units (95% CI: -12.4, 2.8, P=0.003). Furthermore, empagliflozin reduced body mass index (BMI) by -0.560 kg (95% CI: -0.640, 1.46, P<0.0001). Empagliflozin was well tolerated in the patients. Also, no case of hypoglycemia, genital and urinary infections, or diabetic ketoacidosis (DKA) was reported. Conclusion: The present study supported the use of empagliflozin alongside insulin as a treatment option for individuals with T1D. Trial Registration: http:// www.irct.ir, identifier: irct20130610013612N12, Registration date: 12/9/2022).